Development of active natural antimicrobial packaging reconciled with refrigeration or freezing for the conservation of strawberries (Research, Society and Development, 2020)
The objective of this work was to evaluate the quality and conservation of strawberry in fruit refrigeration and freezing in an active packaging system composed of extended polystyrene trays, antimicrobial saches incorporated with clove essential oil and polyvinyl chloride film (PVC). The results showed efficacy of the packaging during refrigeration and freezing, since the stability of the fruit was higher when the antimicrobial sache was used and the sensory analyses complemented the effectiveness of the active packaging, because it met the requirements of the tasters, after 13 days of storage. Therefore, the study proved that the association of low storage temperatures and the development of an active packaging system with natural essential oil increased the shelf life of the fruit, consequently preserved the sensory characteristics, avoided chemical deterioration and ensured the safety of the fruit, because it inhibited microbial growth, besides presenting great potential for application in the food market, aiming to ensure and, or monitor the quality and safety of the tested product.